Implementation of Distance Education from Face to Face Education of an Engineering Program in Science and Food Technology: A Literature Review - J. D. Corona Flores (Universitat Politècnica de València, 2016)
The implementation of distance education from the face to face modality, has boomed in developing countries because of the benefitsit has, achieving greater student enrollment coverage than traditional mode, you cannot achieve. This article provides a study of the state of the art, which considers the factors involved in carrying out the transition from the classroom to the online mode education are, and can be considered as a framework to implement it in different higher educational programs that are in the process of changing the face to face education to the online mode. It also considers the contribution that the theories of distance education have had on the above change.